DIABETIC KETOACIDOSIS - OUR EXPERIENCES - Miolski, Jelena; Ješić, Maja; Kovačević, Smiljka; Blagojević, Jelena; Zdravković, Vera (Medicinski časopis, 2021)
Diabetic ketoacidosis is an acute complication in children with type 1 diabetes mellitus. It is defined if the sugar value is> 11 mmol / l, pH
Keywords: children, diabetes mellitus type 1, diabetic ketoacidosis